The Golgi in Cell Migration: Regulation by Signal Transduction and Its Implications for Cancer Cell Metastasis - Valentina Millarte; Hesso Farhan (The Scientific World Journal)
Migration and invasion are fundamental features of metastatic cancer cells. The Golgi apparatus, an organelle involved in posttranslational modification and sorting of proteins, is widely accepted to regulate directional cell migration. In addition, mounting evidence suggests that the Golgi is a hub for different signaling pathways. In this paper we will give an overview on how polarized secretion and microtubule nucleation at the Golgi regulate directional cell migration. We will review different signaling pathways that signal to and from the Golgi. Finally, we will discuss how these signaling pathways regulate the role of the Golgi in cell migration and invasion. We propose that by identifying regulators of the Golgi, we might be able to uncover unappreciated modulators of cell migration. Uncovering the regulatory network that orchestrates cell migration is of fundamental importance for the development of new therapeutic strategies against cancer cell metastasis.